2017
DOI: 10.3892/mmr.2017.6626
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of PAX9 in patients with esophageal squamous cell carcinoma and its prediction value to radiation sensitivity

Abstract: Abnormal paired box 9 (PAX9) expression is associated with tumorigenesis, cancer development, invasion and metastasis. The present study investigated the prognostic significance of PAX9 in esophageal squamous cell carcinoma (ESCC) and its role in predicting radiation sensitivity. A total of 52.8% (121/229) ESCC tissues were positive for PAX9. The 1-, 3- and 5-year disease-free survival (DFS) rates were 72.2, 35.2 and 5.6%, respectively, and the overall survival (OS) rates were and 86.1, 44.4, and 23.1%, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
0
11
2
Order By: Relevance
“…It is involved in cell proliferation, apoptotic resistance, and cell migration and has been shown to be a prognostic marker of esophageal squamous cell carcinoma. 12 AXIN2 is a negative regulator of the catenin Wnt signaling pathway and is expressed in dental papilla mesenchyme. 5 Mutations in AXIN2 have been associated with tooth agenesis, with the phenotype presenting as a mix of anterior and posterior tooth agenesis.…”
Section: Odontogenesismentioning
confidence: 99%
“…It is involved in cell proliferation, apoptotic resistance, and cell migration and has been shown to be a prognostic marker of esophageal squamous cell carcinoma. 12 AXIN2 is a negative regulator of the catenin Wnt signaling pathway and is expressed in dental papilla mesenchyme. 5 Mutations in AXIN2 have been associated with tooth agenesis, with the phenotype presenting as a mix of anterior and posterior tooth agenesis.…”
Section: Odontogenesismentioning
confidence: 99%
“…In human ESCC tissue samples, PAX9 was found to be lost or downregulated, and progressive loss of PAX9 expression was correlated with increasing malignancy . PAX9 expression was associated with better survival and radiosensitivity . In human OSCC cells, PAX9 expression was essential for cell growth and survival .…”
Section: Introductionmentioning
confidence: 96%
“…To date, only one study has described the role of PAX9 as a predictive marker in cancer. Tan et al (2017) observed an interaction between the expression of this gene and postoperative radiotherapy in esophageal squamous cell carcinoma, wherein patients with high expression showed greater life expectancy and delayed disease reoccurrence, granting this gene a positive role as a marker of radiosensitivity in this type of malignancy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%